KONSTELASI KONFLIK DALAM LEMBAGA PENDIDIKAN: SEBUAH TELAAH KRITIS - Baharuddin Baharuddin (Fak. Tarbiyah UIN Maliki Malang, 2012)
The reality of the conflict in educational institutions is a necessity. Critical policy management institution established in the handling of the conflict affected the development of insight and thought construction personnel organization. Carefully in view of the conflict to the attention of the fundamental management of educational institutions. Simultaneous development of thought in the handling of the conflict must be continuously updated. The fundamental reason of that is the conflict evolved into a symbol of the rich meanings and diverse interpretations. Democracy, growth, and self-actualization is a factor inherent in the interpretation of the conflict in the world of education. Therefore, this paper offers a critical examination of conflict in the world of education as a part in building a solid educational institutions.